TRANSFORMING STUDENT INTO ENTREPRENEURS: THE ROLE OF ENTREPRENEURSHIP EDUCATION AND E-COMMERCE - Harisandi, Prasetyo; Nurhidayah, Rika; Yusriani, Sri; Yuningsih, Nining; Tikaromah, Oom; Sarjaya, Sarjaya (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the impact of entrepreneurship education and e-commerce utilization on students' entrepreneurial interest at Pelita Bangsa University within the digital era. Using a quantitative approach and a survey method, data were collected from 100 students who had completed entrepreneurship courses and had experience utilizing e-commerce platforms. The results, analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), indicate that entrepreneurship education significantly fosters a creative mindset and enhances entrepreneurial motivation. Simultaneously, e-commerce proficiency facilitates market accessibility, thereby increasing students' inclination toward digital entrepreneurship. These findings emphasize the critical interplay between entrepreneurship education and e-commerce in shaping entrepreneurial aspirations. The study contributes to the literature by providing actionable insights for educational institutions to design more robust entrepreneurship curricula and e-commerce training programs, ultimately fostering a generation of skilled digital entrepreneurs in Indonesia.